Financial Leverage and Managerial Compensation: Evidence from Non-Cyclical Industries in Indonesia - Elva Farihah; Okta Sindhu Hartadinata; Afandi Ukik Wahyu Bintang Maulana (Journal of Economics, Business, and Accountancy Ventura, 2023)
This research analyzes the impact of financial leverage on managerial compensation. This study also explores the moderating effect of financial distress on the link between financial leverage and managerial compensation. This study used a quantitative approach with multi-linear regression analysis. The sample consisted of 26 firms from non-cyclical industries listed on the Indonesian Stock Exchange (IDX) from 2018 to 2022, with a total observation of 130. The data research was derived from firms' annual reports. The empirical result shows that financial leverage positively affects managerial compensation. It suggests that firms incentivize management with higher compensation, aiming for more professional leverage management to maximize firm value. This finding is relevant to the trade-off theory. This study also demonstrates that the variable of financial distress is categorized as a pure moderator. It is confirmed that financially distressed firms determine financial leverage as a negotiation tool to reduce the cost of salaries. This finding implies the importance of the firms carefully balancing human capital and compensation schemes because the manager's interest might be given up if the company is in financial distress.